Immune alterations in patients with anti-interferon-γ autoantibodies - Nuttapol Chruewkamlow (2018)
© 2016 Chruewkamlow et al. Autoantibodies against interferon-gamma (IFN-γ) can cause immunodeficiency and are associated with various opportunistic infections. In the present study, we investigated other cellular immune parameters for a better understanding of the immunodeficiency condition in the patients. The numbers of WBC, monocytes and NK cells were increased in patients with anti-IFN-γ autoantibodies (AAbs). Upon TCR activation, T cell proliferation and IL-2 receptor of the patients remained intact. Nonetheless, the Th1 cytokine (IFN-γ and TNF-α) production was up-regulated. The production of Th2 (IL-4) and Th17 (IL-17) cytokines was unchanged. We suggest that, in addition to the presence of anti-IFN-γ autoantibodies, alterations in the cellular immune functions may also contribute to this immunodeficiency.